2009
DOI: 10.1603/029.102.0504
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pesticides on Adult Rove Beetle <I>Atheta coriaria</I> (Coleoptera: Staphylinidae) Survival in Growing Medium

Abstract: The rove beetle Atheta coriaria (Kraatz) (Coleoptera: Staphylinidae) is a natural enemy (biological control agent) commercially available for control of certain greenhouse insect pests, including fungus gnats, shore flies, and thrips. This study assessed the compatibility of pesticides (insecticides and fungicides) used in greenhouses with A. coriaria adults. Treatments were applied to 473-ml deli squat containers half-filled with a growing medium. We evaluated the effects of the pesticides when releases of A.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 37 publications
(34 reference statements)
3
24
0
1
Order By: Relevance
“…israelensis, flonicamid, Metarhizium anisopliae, azadirachtin, and spinosad [77]. Furthermore, none of the pesticides impeded predation of rove beetle adults on fungus gnat (Bradysia sp.…”
Section: Effects Of Pesticides On Dalotia Coriaria and Orius Insidiosusmentioning
confidence: 99%
“…israelensis, flonicamid, Metarhizium anisopliae, azadirachtin, and spinosad [77]. Furthermore, none of the pesticides impeded predation of rove beetle adults on fungus gnat (Bradysia sp.…”
Section: Effects Of Pesticides On Dalotia Coriaria and Orius Insidiosusmentioning
confidence: 99%
“…Reproduction of the aphid predator, Aphidoletes aphidimyza was not indirectly affected after exposure to azadirachtin [119], and azadirachtin did not indirectly affect the fecundity of the parasitoid, Aphidius colemani [120]; longevity and foraging ability of the parasitoids, Cotesia plutellae and Diadromus collaris and sex ratio of progeny [6]; nor reproduction of the predatory mite, Neoseiulus californicus [121]. Cloyd et al (2009) [122] found, under laboratory conditions, that exposure to azadirachtin did not inhibit prey consumption (fungus gnat larvae) of rove beetle, Atheta coriaria adults. However, it was reported by [123] that first instar larvae of Harmonia axyridis, when exposed to azadirachtin, exhibited increased development time whereas there was no indirect affect on adult female fecundity.…”
Section: Azadirachtinmentioning
confidence: 99%
“…Moreover, exposure to B. bassiana reduced the fecundity of N. californicus females [121] whereas the fungus Cephalosporium lecanii exhibited no indirect effects on longevity of the leafminer parasitoid, Diglyphus begini [137]. In another study, conducted under laboratory conditions, [122] reported that exposure to Metarhizium anisopliae had no indirect effect on prey consumption (fungus gnat larvae) of rove beetle, A. coriaria adults. It was shown by [132] that exposure to Isaria (=Paecilomyces) fumosoroseus at a low relative humidity (55%) resulted in no indirect effects on foraging behavior and longevity of the aphid parasitoid, Aphelinus asychis whereas both parameters were significantly reduced when exposed to a high (≥95%) relative humidity, which could impact the ability of the parasitoid to regulate aphid populations.…”
Section: Microbialsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in others, negative effects of soaps applications were found on some groups of natural enemies (Oetting & Latimer, 1995;Smith & Krischik, 2000;Stansly et al, 2002;Kraiss & Cullen, 2008;Raudonis et al, 2010;Hall & Richardson, 2013;Smaili et al, 2014). In the case of essential oils, again some studies reported no negative effect on natural enemies (Echegaray & Cloyd, 2012;González et al, 2013), but some detrimental effects have been also reported (Momen & Amer, 1999;Amer & Momen, 2002;Choi et al, 2004;Bostanian et al, 2005;Huignard et al, 2008;Cloyd et al, 2009).…”
Section: Introductionmentioning
confidence: 98%